1999
DOI: 10.2308/acch.1999.13.1.37
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Formal Mentoring Programs and Perceived Barriers to Obtaining a Mentor at Large Public Accounting Firms

Abstract: One way for firms to promote the mentoring of employees is to establish formal programs that match employees with potential mentors. Whether employees are satisfied with such formal mentoring is an empirical question. This paper examines that issue as well as whether formal mentoring programs serve to reduce perceived barriers to obtaining a mentor. The study is based on survey data obtained from 723 respondents currently working at the major public accounting firms. The study found that certain methods for ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 12 publications
3
54
1
Order By: Relevance
“…In contrast, the importance of participant input into the pairing process was identified by Viator (1999): mentees who had no input into the pairing process were much less satisfied with their mentor. Similarly, Ragins and Cotton (1999) found that informal mentoring relationships spontaneously formed by mentees had greater benefits and mentees had more satisfaction with their mentors than mentees in formal programs where the pairs were formed by a program coordinator.…”
Section: Pairing In Mentoring Programs: Previous Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast, the importance of participant input into the pairing process was identified by Viator (1999): mentees who had no input into the pairing process were much less satisfied with their mentor. Similarly, Ragins and Cotton (1999) found that informal mentoring relationships spontaneously formed by mentees had greater benefits and mentees had more satisfaction with their mentors than mentees in formal programs where the pairs were formed by a program coordinator.…”
Section: Pairing In Mentoring Programs: Previous Studiesmentioning
confidence: 97%
“…They show conflicting results for approaches to the pairing process. Some studies of mentor pairs formed by a program coordinator achieved satisfactory relationships (D'Abate and Eddy 2008;Boice 1992a;Ragins et al 2000), while other studies demonstrated that participant input into the pairing process was preferable (Viator 1999;Ragins and Cotton 1999;Allen et al 2006). In a program where the coordinator matched mentors and mentees based on informal knowledge and biographical data about participants, mentors were extremely satisfied with the pairing process (D'Abate and Eddy 2008).…”
Section: Pairing In Mentoring Programs: Previous Studiesmentioning
confidence: 99%
“…In Australia, Yap (1997) obtains a response rate of 35% from a mixed group of Australian expert users; and Deegan & Rankin (1999) obtain response rates of 25% from groups of senior executives of the largest companies in Australia and also from a range of users. In the US, Hermanson (2000) obtains an overall response rate of 28% across nine groups of users, preparers and auditors in the US; Ashbaugh et al (1999) obtain a response rate of 27% from US listed companies; Ayers & Kaplan (1998) obtain a response rate of 32% from Big Six audit partners; while Thomas, Davis & Seaman (1998) and Viator (1999) obtain response rates of 35% and 30%, respectively, from CPAs. Milne & Chan (1999) obtain response rates of 21% and 25% from investment analysts and accountants, respectively, in New Zealand.…”
Section: Endnotesmentioning
confidence: 99%
“…22 Mentees were more satisfied with their mentoring relationships when there were set goals and objectives and if they have input in the matching process, this improved the satisfaction with their mentor. 23 Mentoring is especially helpful in a situation of 'being stuck'. The mentor acts as a sounding board which enables a can do attitude, inspiring confidence to achieve and help with interpersonal skills.…”
Section: Mentor Motivation and Trainees Career Developmentmentioning
confidence: 99%